MANAGEMENT STYLES AND JOB SATISFACTION - Valencia Pomareda, Pedro Herbert (2014)
From Howthorne experiments, the administration continued looking for the best way to improve the relationships they have with reviewers, is so important to be Leadership in strategic management element, chose among the many leadership styles for the Rensis Liker be the most appropriate technical and more effectively to achieve empowerment, establishing satisfaction that leadership styles Likert looking at our employees, which is why we seek to know the level of job satisfaction that leadership styles Likert, achieved through Herzberg.